Forced Vibration Equation - Abdurahmonova Gulruh Murodullo kizi (International Journal on Integrated Education, 2022)
Processes that are more or less repetitive are called oscillations. Depending on the physical nature of the repetitive process, vibrations are divided into mechanical, electromechanical, electromagnetic and others. We see mechanical vibrations. Vibrations are divided into free (or special) oscillations, forced oscillations, auto oscillations, and parametric oscillations.